2015
DOI: 10.2319/080815-536.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dental crowding and mandibular incisor proclination during orthodontic treatment without extraction of permanent mandibular teeth

Abstract: Objective: To examine changes in mandibular incisor proclination and protrusion resulting from alleviation of crowding. Materials and Methods: Records of 96 patients from a private practice treated without extractions or interproximal enamel reduction in the mandibular arch were included. Pre-and post-treatment cephalograms and models were examined to determine changes in incisor proclination, protrusion and crowding. Results: For every millimeter of crowding alleviation, increases in incisor proclination (DIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The results from this finding demonstrate two movements, first by round archwires and subsequently, by rectangular archwires. Other studies 5 - 8 , 27 , 29 reported the results from total treatment with durations of more than a year and included the finishing phase, which may affect the mandibular incisor position from wire bending, torqueing or intermaxillary elastics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results from this finding demonstrate two movements, first by round archwires and subsequently, by rectangular archwires. Other studies 5 - 8 , 27 , 29 reported the results from total treatment with durations of more than a year and included the finishing phase, which may affect the mandibular incisor position from wire bending, torqueing or intermaxillary elastics.…”
Section: Discussionmentioning
confidence: 99%
“…2 Results of very effective dental changes early in treatment after alignment and leveling showed that proclination of mandibular incisors was common, 3 especially in non-extraction orthodontically-treated cases. [4][5][6][7][8] Proclination of mandibular incisors may affect the esthetic outcome, surrounding periodontal tissues, 9 and treatment stability. 10 To correct crowded teeth, labial displacement of incisors is expected to gain spaces for tooth alignment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The preservation of inter-canine width has been advocated to increase long-term stability in the mandible and, if IPR is used to gain space rather than expanding in the lower anterior region, the inter-canine width is more likely to be preserved. 19,20 A study examining cases 10 years post-retention investigated the long-term stability of treatment-induced changes of the maxillary and mandibular arch forms. 21 It was found that the arches tended to return to their pretreatment shape and that pretreatment arch form is the best guide for future arch form stability.…”
Section: Increased Stabilitymentioning
confidence: 99%
“…With an increasing number of patients using removable, aesthetic, orthodontic appliances, for whom extractions are often not advocated, the use of IPR as an alternative to gain space is becoming more popular. 5,20 The benefit of using IPR rather than extraction therapy to gain space is that it decreases overall treatment time, since the amount of stripping corresponds exactly with the amount of crowding. 27 Performing IPR when treating a case without any extractions also means that excessive advancement of the mandibular incisors can be avoided, 28 as well as overexpansion of the dental arches, while at the same time satisfactory alignment is still achieved.…”
Section: Extraction Avoidancementioning
confidence: 99%